2018
DOI: 10.1007/s00401-018-1952-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of histopathology and NAB2–STAT6 fusion subtype in classification and grading of meningeal solitary fibrous tumor/hemangiopericytoma

Abstract: Meningeal solitary fibrous tumor (SFT)/hemangiopericytoma (HPC) is a rare tumor with propensity for recurrence and metastasis. Although multiple classification schemes have been proposed, optimal risk stratification remains unclear, and the prognostic impact of fusion status is uncertain. We compared the 2016 WHO CNS tumor grading scheme (CNS-G), a three-tier system based on histopathologic phenotype and mitotic count, to the 2013 WHO soft-tissue counterpart (ST-G), a two-tier system based on mitotic count alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…32 In fact, the association between the fusion variants and malignant potential is still unclear, and few studies have evaluated whether malignant SFTs have additional alterations compared to nonmalignant SFTs. 9,[31][32][33]39,41,45 Recent reports have suggested that TERT promoter mutations ( Fig. 4d) are associated with poor prognosis in SFTs.…”
Section: Molecular Factors Associated With Clinical Evolutionmentioning
confidence: 97%
See 4 more Smart Citations
“…32 In fact, the association between the fusion variants and malignant potential is still unclear, and few studies have evaluated whether malignant SFTs have additional alterations compared to nonmalignant SFTs. 9,[31][32][33]39,41,45 Recent reports have suggested that TERT promoter mutations ( Fig. 4d) are associated with poor prognosis in SFTs.…”
Section: Molecular Factors Associated With Clinical Evolutionmentioning
confidence: 97%
“…The NAB2–STAT6 fusion is the molecular hallmark (Fig. d) of SFTs . Although Barthelmess et al detected a significant association between the NAB2ex6‐ STAT6ex16/17 variant and malignancy in SFTs, other authors have reported that no fusion variants are associated with malignancy …”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations